2000
DOI: 10.1074/jbc.275.2.1327
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Gβγ Is Required for Membrane Targeting and Palmitoylation of Gαs and Gαq

Abstract: Peripheral membrane proteins utilize a variety of mechanisms to attach tightly, and often reversibly, to cellular membranes. The covalent lipid modifications, myristoylation and palmitoylation, are critical for plasma membrane localization of heterotrimeric G protein alpha subunits. For alpha(s) and alpha(q), two subunits that are palmitoylated but not myristoylated, we examined the importance of interacting with the G protein betagamma dimer for their proper plasma membrane localization and palmitoylation. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
158
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(175 citation statements)
references
References 62 publications
17
158
0
Order By: Relevance
“…Constructs-Wild type ␣ s (HA-tagged) and ␤-binding-deficient mutant ␣ s IEKϩ(HA-tagged) were described previously (10). The expression vector for ␤ 1 (Myc-and His-tagged) was provided by David P. Siderovski (University of North Carolina) (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Constructs-Wild type ␣ s (HA-tagged) and ␤-binding-deficient mutant ␣ s IEKϩ(HA-tagged) were described previously (10). The expression vector for ␤ 1 (Myc-and His-tagged) was provided by David P. Siderovski (University of North Carolina) (9).…”
Section: Methodsmentioning
confidence: 99%
“…Cell Fractionation Assay-Soluble and particulate fractions were isolated as described previously (10). Briefly, 48 h after transfection HEK293 cells were washed in ice-cold PBS and lysed in hypotonic lysis buffer (50 mM Tris-HCl, pH 8, 2.5 mM MgCl 2 , 1 mM EDTA, 1 mM dithiothreitol) with protease inhibitors (0.5 mM phenylmethylsulfonyl fluoride, 5 g/ml leupeptin, 5 g/ml aprotinin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A control experiment showed that a q was effectively pulled down by b 1 g 2 , whereas a mutant of a q (a q IE), previously reported to be b 1 g 2 -binding defective, did not show any binding (Figure 7) (Evanko et al, 2000). The point mutants a 13 G205S, a 13 K204E, a 13 E229K, a 13 R232E, and the double mutants a 13 K204E/E229K and a 13 E229K/ R232E also bound to Myc-His b 1 g 2 dimers, indicating that these mutations do not affect the structural integrity of a 13 .…”
Section: Resultsmentioning
confidence: 99%
“…All α subunits of heterotrimeric G-proteins (with the exception of transducin) are reversibly modified by palmitoylation, i.e., the attachment of palmitate to a cysteine residue near the N-terminus (reviewed in Chen and Manning (2001), Mumby (1997), Smotrys and Linder (2004), Wedegaertner (1998)). The second major determinant of G-protein localization is the anchoring of the Gβγ subunits to the membrane (Evanko et al, 2001(Evanko et al, ,2000.…”
Section: Light Regulation Of G Q α Translocation and Morphological Chmentioning
confidence: 99%